2002
DOI: 10.1128/cdli.9.3.568-572.2002
|View full text |Cite|
|
Sign up to set email alerts
|

Predicting Kala-Azar Disease Manifestations in Asymptomatic Patients with LatentLeishmania donovaniInfection by Detection of Antibody against Recombinant K39 Antigen

Abstract: Clinically visceral leishmaniasis is suspected in only a fraction of infected persons, as the majority of these may not have clinical manifestations and remain asymptomatic. There is scanty information on diagnosing latent infections and predicting disease in asymptomatic persons. We therefore carried out a study on asymptomatic contacts of patients with visceral leishmaniasis and post-kala-azar dermal leishmaniasis by using methods for detection of antibody to recombinant K39 (rK39) antigen. A total of 240 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 11 publications
7
42
0
2
Order By: Relevance
“…One explanation might be that individuals with VL do not show complete elimination of the parasite. This agrees with the opportunistic occurrence of the diseases, as observed in patients with AIDS [19][20][21][22][23][24][25].…”
Section: Medicationsupporting
confidence: 78%
“…One explanation might be that individuals with VL do not show complete elimination of the parasite. This agrees with the opportunistic occurrence of the diseases, as observed in patients with AIDS [19][20][21][22][23][24][25].…”
Section: Medicationsupporting
confidence: 78%
“…In Sudan, Uganda, India and Afghanistan, validation studies of the rK39 rapid test yielded sensitivities that ranged from 67-100%. Despite the variability in the sensitivity, these studies reported similar specificities (95-100%) (Zijlstra et al 2001, Singh et al 2002, Chappuis et al 2005, Ritmeijer et al 2006) and this finding is in agreement with the results of the current study.…”
Section: Discussionsupporting
confidence: 83%
“…A similar relationship between the high occurrence of clinical VL and high antibody titers was reported in the works by Singh and others. 20,27 The same works also noted that antirK39 IgG titer in serum correlated with the parasite load and that persistent increase of antibody titers related to clinical unresponsiveness to antileishmanial treatment. The prevalence by rKRP42 urine ELISA alone does not seem to be useful, because in the first test, the highest rate was recorded in center 2 (Tables 1 and 2); however, the clinical rate there turned out to be the lowest, with only one sporadic VL case.…”
Section: Discussionmentioning
confidence: 70%
“…18,19 Moreover, early diagnosis and treatment may reduce the chance of disease transmission. A study conducted in Bihar state, India, reported that 69% of asymptomatic seropositives by rK39 ELISA and dipstick developed kala-azar within 1 year, 20 suggesting that many of the asymptomatic seropositives were in a pre-clinical state.…”
Section: Introductionmentioning
confidence: 99%